Evaluation and Application of Milan System in Cyto-Diagnosis of Salivary Gland Lesions at Tertiary Care Teaching Hospital - Marvaniya, Arzoo Mansukhbhai; Dhotre, Sanjay Vinayak; Barot, Hitendra Pravinkumar; Dave, Pooja; Presswala, Heli Bharatbhai; Parikh, Kajal (Annals of Pathology and Laboratory Medicine, 2025)
Background: Fine needle aspiration cytology (FNAC) of salivary gland lesions is an inexpensive, minimally invasive, easier to perform and outpatient diagnostic procedure, which is helpful to clinicians for earlier diagnosis and treatment because of rapid turnaround time. Methods: The present study is conducted retrospectively over a period of one year to classify salivary gland lesions according to Milan system; all patients were subjected to FNAC by using 22-24 gauge needle attached to a 10 ml syringe, with at least two needle passes were made for each patient. Smears are stained an analyzed under light microscopy. Results: Out of total (n=80) cases the number of cases in each category were: non-diagnostic 15% and 85% were diagnostic. Out of 85% diagnostic cases, neoplastic lesions were observed in 57.5% of patients, non-neoplastic lesions in 27.5% of patient. Conclusion: Fine needle aspiration cytology is a reliable examination, providing important information to the surgeon in the preoperative diagnostic assessment when Milan system was applied.